Lateral communities, vertical cities: understanding the nature of the livelihood strategies utilized by former residents of the Pine Road informal settlement in the pickwick transitional housing development - Made, Ayanda (School of Architecture, Planning and Geomatics, 2025)
In addressing the lack of affordable housing in South Africa, 15% of South Africa's 14.45 million households earn enough to secure a mortgage, and 60% earn less than R3500.00 a month and can qualify for state housing. The remaining 25%, including most teachers, nurses, police officers and soldiers have had access to neither (Marutlulle, 2021). This leaves a missing rung in the housing ladder due to the nature of South Africa's unemployment rate. Social Housing is currently the only housing model available and leaves many South Africans unable to access the resource exacerbating the existing backlog. Currently, South Africa doesn't have an established transitional housing model that caters to households on very low and inconsistent incomes earning between R0 - R3500. It is not an official government policy, nor does it have an established funding stream or programme. In its current state, it exists either as a developing practice or a compelling concept. (Development Action Group, 2022) For these households, formal government-subsidised or private housing options in suitable areas do not exist. The Development Action Group (DAG) together with the City of Cape Town (CoCT) and the National Association of Social Housing Organisations (NASHO) established the Pickwick Transitional Housing Facility in Salt River, Cape Town. This is the first attempt to provide transitional housing on well-located land close to the city centre (DAG, 2022). This type of housing model can form one element of broader psychosocial and economic support programmes for people who earn very low and inconsistent incomes, therefore the aim of the research is to assess if and how moving from the Pine Road informal settlement in Woodstock to the formal Pickwick Transitional Housing development in Salt River has possibly impacted the livelihood strategies of the residents. In order to inform the development of a transitional housing model that responds to the South African context built around supporting the livelihood strategies of very low, inconstant income and/or unemployed households. The study will be qualitative in nature, using a relevant literature review and a Case and Ethnographic study as research methods.